Feasibility and performance of a patient-oriented discharge instruction tool for heart failure. Issue 3 (19th August 2019) - Schofield, Toni; Ross, Heather; Bhatia, R Sacha; Okrainec, Karen
Abstract : Background: The provision of patient-centred discharge instructions is a pivotal goal for improving quality of care for patients with heart failure (HF) during care transitions. We tested the feasibility and performance of a novel discharge instruction tool co-designed with patients and adapted for HF; the patient-oriented discharge summary (PODS-HF) with the aim of improving communication, comprehension and adherence to discharge instructions. Methods: An iterative process was used to adapt and implement an existing patient instruction tool for patients with HF (PODS-HF). A mixed methods approach was then used to explore patient experience, feasibility and performance using a pre–post study design among eligible patients admitted for HF over a 6-month period. Outcome measures included: the documentation of patient-centred instructions, a locally derived Average Discharge Score (ADS) based on the inclusion of instructions in nine key areas, patient satisfaction and understanding and adherence to instructions at 72 hours and 30 days determined using follow-up phone calls. Results: 19 patients were enrolled. The ADS increased by 68% with more consistent documentation. Patient satisfaction remained high. Patients provided PODS-HF reported receiving written information about HF related signs and symptoms to watch for (two out of five patients in the usual care group vs seven out of seven patients in the PODS-HF group; p=0.045). Patients also felt more confident to manage their own health and 30-day adherence to diet and exercise instructions improved while reducing the need for unscheduled visits. Quantitative results were supported by themes identified during follow-up calls, namely, the utility of written instructions and the importance of a follow-up call. Conclusion: PODS-HF is a feasible tool for the delivery of patient-centred discharge instructions for patients with HF. The individual benefits of clarification and reinforcement made during follow-up calls among patients receiving this tool remains to be clarified.